SISTEM INFORMASI GEOGRAFIS UNTUK ANALISA SPASIAL PENENTUAN DAERAH RAWAN KECELAKAAN LALU LINTAS (STUDI KASUS : KOTA PEKANBARU) - M. Haris Wandra; Mardhiah Fadhli (ABEC Indonesia, 2021)
Quoted from the official Pekanbaru Government portal, Pekanbaru City is one of the Metropolitan Cities in Indonesia, which has a higher accident potential, based on data obtained from the Pekanbaru City Traffic Unit which is summarized from 2016-2019. However, people in Pekanbaru City have not realized it because of the lack of information about the high number of accidents in Pekanbaru City. In addition, the information prepared by the police agency is only in the form of a few warning signs. Geographic Information System is a data management system that has spatial information or the ability to build, store, manage and display geographic references in a database. With the Spatial Analysis of the Location of Accident-Prone Areas Web-Based, it can help the police and the public in finding out information on locations that are prone and not prone to using spatial analysis, so that people can be more careful in driving and know the points of locations that are prone and not prone to accidents in Pekanbaru City. This system uses theframework CodeIgniter, in mapping using leaflet js and using thefeatures Overlay and Buffer. Based on the results oftesting blackbox testing and user acceptance test that the system functions as expected and usability testing with 20 people stating that 93% of the people agree with this system.